EFEITO DO GRUPO GENÉTICO E PESO DE ABATE NAS CARACTERÍSTICAS DA CARCAÇA E QUALIDADE DA CARNE DE CORDEIROS CONFINADOS - LANDIM, Aline Vieira (2008)
Sheep rearing is becoming an important economic activity, where it is necessary to establish the ideal slaughter weight per genetic group and sex to acheive standardized carcasses which meet customer needs in terms of product quality.This experiment evaluated the effect of genetic group and slaughter weight on carcass traits and meat quality in lambs. Twenty four Santa Ines (SI), 24 ½ Ile de France x ½ Santa Inês (ILE x SI) and 8 ½ Texel x ½ Santa Inês (TE x SI), slaughtered at different weights (30, 35, 40 and 45 kg ) were used.Eye rib area and fat thickness were measured in vivo and on the carcass. After a 16 hour food and water fast the animals were slaughtered conventionally and the carcasses placed in a cold chamber at 4ºC/24h. pH was measured at slaughter and after 24h as were subjective measurements on the Longissimus dorsi. A section of the rib region from the 11th to 13th ribs of the left side of the carcass was used for tissue and fractional composition, physic-chemical parameters and fatty acid composition. The experiment was in a 3 x 2 x 4 factorial design. For physic-chemical and fatty acids a 3 x 4 factorial and analysed using CORR (Correlation), REG (Regression) and Duncan (5%) means test in SAS ®. Genetic group did not influence (P>0.05) means for rib eye area or fat thickness measured by ultrasound or paquimeter. These measurements increased with slaughter weight. Tissue composition was influenced by genetic group and slaughter weight (P<0.05). The Texel x Santa Inês had most muscle (63.75 g), fat (53.75 g), bone (29.37 g) and edible portion (78.75%) at 35 and 45 kg . Slaughter weight centesimal composition, with an increase in total lipids as weight increased. No significant differences were found for final pH between genetic groups and slaughter weights. Genetic group did not influence colour (3.32), shear force (3.57 kgf) or loss in cooking (24.05%) of the Longissimus dorsi, but slaughter weight affected these, causing stronger colour, tougher meat and greater loss in cooking as slaughter weight increased. Significant differences were found in the sensorial traits of the meat with different genetic groups and slaughter weights. The fatty acids found included oleic (43%); palmitic (22%) and estearico (18%). Higher quantities of desirable fatty acids were found in the Texel x Santa Inês (66.78%) group. Slaughter weight caused a significant difference (P<0.05) in the fatty acid profile of saturated and polyunsaturated fats.